God : A Human History - Reza Aslan (London Bantam Press, 2017)
Explores humanity's attempts to comprehend the divine by giving it human traits and emotions, and calls for a more expansive understanding of God to develop a more universal spirituality
Include Note and Index
Keywords: God -- Religions -- History